A Review of Logistic Management, Knowledge Management and E-business - How is Malaysia's E-business Development and Logistics Management Practices Now? - Nurul Izzah, Mohd Shah; Liu, Yao; Damhuji, Rifai (JSRAD, 2015)
The term ‘‘logistics management and e-business’’ has been in use for more than 10 years, but has recently become an important subject of analysis and empirical investigation. Beginning with a literature review, this paper presents and discusses the features of e-business and also role with importance of logistics management in ebusiness development systems. The following questions are considered; (1) How is e-business and logistics management defined? (2) How development of e-business and logistics management industries in Malaysia? And, (3) How the dimensions of e-business development and logistics management been integrated into knowledge management?